Cultural districts - Lavanga, Mariangela (Edward Elgar Publishing, 2020)
Academic literature on cultural districts has skyrocketed. In parallel, the development of cultural districts has become a standard practice in policy-making worldwide at different scales. Government bodies have used cultural districts policies to regenerate and rebrand urban areas, sometimes focusing on increasing cultural consumption, other times fostering innovation and entrepreneurship. This chapter first provides a definition of cultural district and discusses its roots in the Marshallian industrial district. Secondly, it looks at the agglomeration economies that firms, organizations and individuals enjoy because they are not only co-located in the same area but highly interconnected among each other. In conclusion, the study of cultural districts offers a challenging and fertile ground to advance theories on cultural industries and urban development while re-affirming the importance of intense face-to-face interaction and spatial proximity in the production, distribution and consumption of cultural goods and services.